Distinct gut bacterial composition in Anoplophora glabripennis reared on two host plants - Wang, Xuefei; Wang, Hualing; Zeng, Jianyong; Cui, Zezhao; Geng, Shilong; Song, Xiaofei; Zhang, Fengjuan; Su, Xiaoyu; Li, Huiping (Frontiers in Microbiology, 2023)
Anoplophora glabripennis is an invasive wood borer pest that has caused considered damage to the forestry. Gut bacteria is of great importance in biology and ecology of herbivores, especially in growth and adaptation, however, the community change of the pest feeding on different hosts was largely unknown. In this study, we investigated the gut bacterial communities of A. glabripennis larva fed on different preferred hosts Salix matsudana and Ulmus pumila using 16S rDNA high-throughput sequencing technology. A total of 15 phyla, 25 classes, 65 orders, 114 families, 188 genera and 170 species were annotated in the larva gut of A. glabripennis fed on S. matsudana or U. pumila . The dominant phya were Firmicutes and Proteobacteria and the core dominant genus were Enterococcus, Gibbsiella, Citrobacter, Enterobacter, Klebsiella. Significantly higher alpha diversity appeared in U. pumila than that in S. matsudana and significantly differences of gut bacterial communities showed between two host plants based on PCoA analysis. The species with significant abundance differences between the two host plants were Gibbsiella, Enterobacter, Leuconostoc, Rhodobacter, TM7a, norank, Rhodobacter, and Aurantisolimonas, indicating that the abundance of larval gut bacteria was affected after feeding different hosts. Further network diagram showed that the complexity of the network structure and the modularity were higher in U. pumila than in S.matsudana, suggesting that the gut bacteria in U. pumila were more diverse. The dominant role of most gut microbiota was related to fermentation and chemoheterotrophy, and OTUs were positively correlated with different functions were reported. Our study provided an essential resource for the gut bacteria functional study of A. glabripennis associated with host diets.